2013
DOI: 10.1088/0953-8984/25/38/385701
|View full text |Cite
|
Sign up to set email alerts
|

Phase diagram and annealing effect for Fe1+δTe1−xSxsingle crystals

Abstract: The excess Fe atoms which unavoidably exist in the Fe(Te, Se, S) crystal lattice result in a complicated antiferromagnetic ground state as well as the suppression of superconductivity. As a result, there are still discrepancies on their phase diagrams. In this paper, we report the synthesis of Fe1+δTe1-xSx (0 ≤ x ≤ 0.12) single crystals by a melting method. Superconductivity was greatly improved after air annealing by which we partially removed the excess Fe atoms. Based on the resistivity and susceptibility m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…The blue solid squares and the red solid circles represents T N and T c , respectively. The FeS 1-x Te x single crystals with low-S doping region were reported by a previous report [27] Fig. 4 Magnetic field dependence of the Hall resistivity for a x = 0, b x = 0.02, c x = 0.05, and d x = 0.11 single crystals at various temperatures region after the SC-I is suppressed until disappears.…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…The blue solid squares and the red solid circles represents T N and T c , respectively. The FeS 1-x Te x single crystals with low-S doping region were reported by a previous report [27] Fig. 4 Magnetic field dependence of the Hall resistivity for a x = 0, b x = 0.02, c x = 0.05, and d x = 0.11 single crystals at various temperatures region after the SC-I is suppressed until disappears.…”
Section: Resultsmentioning
confidence: 70%
“…For comparison, the corresponding data of FeS 1-x Te x (1 ≤ x ≤ 0.88) single crystals taken from Ref [27] are also included. For the rich-Te region, the longranged AFM phase T N gradually decreases from 70 K with increasing of S doping, and it coexists with the region of the superconducting phase (SC-II) between 0.95 and 0.89 [27], exhibiting a common property of the iron-based superconductors [22,28]. However, the phase diagram for x < 0.88 is restricted because of the solubility limitation of S. For the rich-S region on the right, superconducting (SC-I) is gradually suppressed from 4.6 K, exhibiting an approximate linear dependence on the Te content.…”
Section: Resultsmentioning
confidence: 99%
“…It changes from commensurate ordering with the (π, 0) propagation vector for FeTe to incommensurate one and finally the magnetic scattering is rapidly suppressed for samples with the S content ∼ 5%. Moreover, the resistivity and susceptibility measurements reveal a coexisting region of superconducting and antiferromagnetic states in the range of x ∈ (0.03, 0.1) [13,15]. Thus, the superconducting state appears in the system with the stable AFM1 phase.…”
Section: Spin Arrangements Vs Crystal Structurementioning
confidence: 99%
“…Unlike the Fe(Te,Se) series, there exists the solubility limit of 30% S content in Fe(Te,S) caused by a large difference between S and Te ionic radii [16]. Previously, it was indicated that the limit is 15% S or even less [14,15], which is probably mainly the result of a difference between nominal and final compositions of studied samples. It seems that both Se and S substitutions suppress the magnetic order of FeTe thereby leading to the superconducting state.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation